(untitled) (Texas Journal of Philology, Culture and History, 2023)
The article analyzes the question of the compatibility of Arabic adaptations with the original in the works of Ishaq Khan and Ibrat. Borrowed words in "History of Ferghana" were lexically-semantically analyzed.